ERROR ANALYSIS OF SIMPLE PRESENT TENSE SENTENCES IN ENGLISH BY INFORMATION SYSTEMS STUDENTS - Eka Resty Novieta Sari (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2021)
This research is a qualitative descriptive research. The purpose of this study was to determine students' understanding in making simple sentences with simple present tense patterns, the types of grammatical errors made by students in making simple sentences with simple present tense patterns, grammatical errors that generally occur in making simple sentences with simple present tense patterns. The subjects of this research are students of semester 1, class A, Information Systems study program. The data collection technique was done by written test. In the written test, the researcher used a written test instrument in the form of English questions about the simple present tense. The written test questions are in the form of multiple choice and essay. The test questions are divided into 3 parts in the tryout test, namely completing sentences, making sentences, and translating sentences. In the third meeting, students complete sentences, answer questions and make a simple present tense paragraph. Based on the research, it was found that: after students were given another explanation about simple present tense sentences, 20 students out of 27 students (74%) answered using simple present tense sentences correctly. It can be said that there has been a 26% increase in understanding of simple present tense sentence patterns.